The first UK report of a rare Cryptosporidium hominis genetic variant isolated during a complex Scottish swimming pool outbreak. Issue 3 (28th March 2021) - Polubotho, Padmaja; Denvir, Lucy; Connelly, Lisa; Anderson, Eleanor; Alexander, Claire L.
Abstract : Cryptosporidium species are responsible for causing the majority of parasite-related gastrointestinal infections in the UK. This report describes an outbreak of 12 laboratory-confirmed cryptosporidiosis cases identified as part of a Scottish swimming pool investigation, with 9 primary and 3 secondary cases occurring over an 8-week period. Molecular speciation was successful for 11/12 cases, which revealed 10 Cryptosporidium hominis cases and 1 Cryptosporidium parvum case. Of the 10 C . hominis cases, further typing identified 7 as being an unusual sub-type, IbA6G3, which is the first description in the UK of this rare variant. The remaining three C. hominis cases were identified as the common IbA10G2 subtype. Following implementation of control measures on two occasions, no further cases were reported. This report highlights the importance of molecular typing to identify and characterize outbreaks, and emphasizes the need to adhere to swimming pool guidance. It also raises awareness of the potential for outbreaks to involve multiple species/sub-types, and emphasizes the importance of strong public health leadership to ensure effective multi-agency investigations and management of outbreaks.